Distinctness and Complexity of E-Learning Influence on the Teacher's Psychology - Buniak, Nadiia; Chala, Теtiana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The golden age and expansion of online technologies cause significant transformations not only in the Ukrainian community. At present, e-learning technologies have gained wide recognition due to the improved accessibility to educational - scientific and methodological materials, and thus, save time and transparency of educational process.It is noted that the use of distance education has the advantage of removing psychological barriers to communication, blurs boundaries. This technology of the educational process is invaluable in the period of quarantine restrictions, as it guarantees the absence of direct contact between people, allows active learning even during illness or self-isolation.It was found that significant technical factors in reducing the success of student learning are technical and psychological unwillingness of teachers to work online.However, we have faced a number of psychological problems posed by this type of learning, especially the experience of burnout feeling, observed among teachers.The purpose of the paper is to analyze the features of e-learning technologies impact on the teacher's psychology, which cause burnout feeling; to analyze the advantages and disadvantages of the online format of knowledge acquisition.The symptoms of emotional burnout are complicated physiological responses of the human body: poor sleep, fatigue, drowsiness, psychosomatic diseases and destructive psychological conditions such as stress, bad mood, depression, apathy, high levels of neuroticism, emotional excitability, increased anxiety, fear, predominance of asthenic emotions, irritability, and the reason is at the back of the situation of “getting out of one’s comfort zone”, forced seclusion need caused by trials for both motherland and all humanity.
Keywords: e-learning technologies; quality of distance education; psyche; situation of “getting out of one’s comfort zone”; physiological responses of the human body; emotional burnout